The IceCube Neutrino Observatory - Contributions to ICRC 2017 Part II: Properties of the Atmospheric and Astrophysical Neutrino Flux - Aartsen, MG; Ackermann, M; Adams, J; Sarkar, S; IceCube Collaboration (Sissa Medialab srl, 2017)
Papers on the properties of the atmospheric and astrophysical neutrino flux submitted to the 35th International Cosmic Ray Conference (ICRC 2017, Busan, South Korea) by the IceCube Collaboration Contents: 1 - Search for Astrophysical Tau Neutrinos in Six Years of High-Energy Starting Events in IceCube 2 - Multi-flavour PeV neutrino search with IceCube 3 - High Energy Astrophysical Neutrino Flux Measurement Using Neutrinoinduced Cascades Observed in 4 Years of IceCube Data 4 - A Measurement of the Diffuse Astrophysical Muon Neutrino Flux Using Eight Years of IceCube Data 5 - Characterizing the Flux of Atmospheric Neutrinos with IceCube-DeepCore 6 - Measurement of High Energy Neutrino – Nucleon Cross Section and Astrophysical Neutrino Flux Anisotropy Study of Cascade Channel with IceCube 7 - Observation of Astrophysical Neutrinos in Six Years of IceCube Data 8 - All-flavor Multi-Channel Analysis of the Astrophysical Neutrino Spectrum with IceCube 9 - Differential limit on an EHE neutrino flux component in the presence of astrophysical background from nine years of IceCube data 10 - Improving Future High-Energy Tau Neutrino Searches in IceCube 11 - Search for Astrophysical Tau Neutrinos with the IceCube Waveforms